2014
DOI: 10.2136/sssaj2013.09.0422
|View full text |Cite
|
Sign up to set email alerts
|

Soil Organic Carbon Sequestration Rates under Crop Sequence Diversity, Bio‐Covers, and No‐Tillage

Abstract: Climate change may be mitigated through soil organic C (SOC) storage under no‐tillage; however, crop management influences on SOC are not well defined in all systems. Our objective was to compare long‐term C fluxes under two no‐tillage sites at Research and Education Centers in Milan (RECM) on Oxyaquic Fragiudalfs and at Middle Tennessee (MTREC) on a Typic Paleudalf in a split‐block design with four replications. The whole‐block was cropping sequences of corn (Zea mays L.), soybeans [Glycine max (L.) Merr.], a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 19 publications
1
32
0
Order By: Relevance
“…Insect populations may also be reduced, predominately because cover crops provide habitat for beneficial insects that regulate population levels (Creamer and Baldwin, 1999;Tillman et al, 2004). Incorporating cover crops during the offseason, as well as including greater temporal cropping diversity also reduces erosion and increases soil organic carbon (SOC), which has been reported previously by authors (Ashworth et al, 2014).…”
Section: Impact Of Crop Rotations and Soil Amendments On Long-term Nomentioning
confidence: 86%
See 2 more Smart Citations
“…Insect populations may also be reduced, predominately because cover crops provide habitat for beneficial insects that regulate population levels (Creamer and Baldwin, 1999;Tillman et al, 2004). Incorporating cover crops during the offseason, as well as including greater temporal cropping diversity also reduces erosion and increases soil organic carbon (SOC), which has been reported previously by authors (Ashworth et al, 2014).…”
Section: Impact Of Crop Rotations and Soil Amendments On Long-term Nomentioning
confidence: 86%
“…Previous research has also shown that poultry litter applications can serve to increase soybean yield (Adeli et al, 2005). This could also be due to the stimulation of SOC formation under greater flushes of N and P (Table 2) which are required for microbial biomass assimilation and correlated to microbial biomass C (DeForest and Scott, 2010;Ashworth et al, 2014). Similarly, an 8-yr study conducted in Illinois found no soybean yield benefits from the inclusion of cover crops into cropping rotations (Olson et al, 2010).…”
Section: Soil Amendment Influence On Long-term Soybean Yieldmentioning
confidence: 97%
See 1 more Smart Citation
“…Poultry litter has proven to increase fertility and meet crop N requirements (Endale et al, 2004; Tewolde et al, 2010). In addition to direct crop benefits from soil fertility, ancillary benefits include liming of acidic soils, as well as organic matter additions (Ashworth et al, 2014). Poultry litter applications and subsequent green manure (e.g., winter weed growth due to a flush of P and N) can alter soil chemical and subsequent biological profiles over time, although the extent of this is largely unknown.…”
mentioning
confidence: 99%
“…After 9 years of cultivation, This effect is mainly attributed to the conservation of soil structure promoted by NT-protected SOM against rapid microbial decomposition, because interaction of SOM and structure protects SOM from oxidation, which maximize recalcitrant C formation and increase stable C fractions (Blanco-Canqui & Lal, 2004). Additionally, crop rotation also contributes to enhance C sequestration under NT compared with CT, due to more diverse substrate and exudates in aboveground and belowground residues (Ashworth et al, 2014;Franzluebbers, Stuedemann, Schomberg, & Wilkinson, 2000).…”
Section: Discussionmentioning
confidence: 99%